Stop the academic world, I wanna get off in the Quai de Branly. Of sketchbooks, museums and anthropology - Ramos, M. J. (Cadernos de Arte e Antropologia, 2015)
Drawing as part of ethnographic observation practices has been systematically undervalued in anthropology, due to an academic tradition that has long favoured realist writing. Yet, sketching, not only as part of one’s fieldwork activities, but as a means to convey one’s first-hand impressions and interpretations can be given some room in academic publishing, if its rules are to be tweaked and image-recognition and tagging are introduced. To help make this case, this article presents the reader-viewer with a practical instance of interaction between field notes and drawings produced during a series of visits to the Parisian museum of Quai de Branly, as means to a reflexion about the potential of drawing in anthropology’s teaching and research practices.